2001
DOI: 10.1074/jbc.m004649200
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Signaling Uses Activin and Transforming Growth Factor-β Receptor-regulated Smads

Abstract: Nodal, a member of the transforming growth factor ␤ (TGF-␤) superfamily, is implicated in many events critical to the early vertebrate embryo, including mesoderm formation, anterior patterning, and left-right axis specification. Here we define the intracellular signaling pathway induced by recombinant nodal protein treatment of P19 embryonal carcinoma cells. Nodal signaling activates pAR3-Lux, a luciferase reporter previously shown to respond specifically to activin and TGF-␤. However, nodal is unable to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 45 publications
3
79
1
Order By: Relevance
“…The canonical Nodal signaling resembles the TGF-b/ Smad pathway (Kumar et al, 2001;Derynck and Zhang, 2003;Massague et al, 2005). Nodal binds to a membrane serine/threonine kinase receptor complex consisting of type I (ALK4 or ALK7) and type II (ActRIIA or ActRIIB) serine/theronine kinase receptors to activate Smad2 and Smad3 (Kumar et al, 2001;Reissmann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The canonical Nodal signaling resembles the TGF-b/ Smad pathway (Kumar et al, 2001;Derynck and Zhang, 2003;Massague et al, 2005). Nodal binds to a membrane serine/threonine kinase receptor complex consisting of type I (ALK4 or ALK7) and type II (ActRIIA or ActRIIB) serine/theronine kinase receptors to activate Smad2 and Smad3 (Kumar et al, 2001;Reissmann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nodal binds to a membrane serine/threonine kinase receptor complex consisting of type I (ALK4 or ALK7) and type II (ActRIIA or ActRIIB) serine/theronine kinase receptors to activate Smad2 and Smad3 (Kumar et al, 2001;Reissmann et al, 2001). The phosphorylated Smad2/3 proteins bind to Smad4 and subsequently undergo nuclear translocation, allowing for the assembly of active transcription complexes on the promoter of Nodal target genes (Schier, 2003;Massague et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…First, Nodal can bind to the activin receptor complex containing activin receptors IIB and IB (ALK4) (19,23,24). Signaling of Nodal through this receptor complex requires Cripto since, in the absence of Cripto, Nodal loses its signaling activity through the activin receptor complex (19,(23)(24)(25). The other receptor complex that mediates Nodal action is activin receptor IIB-ALK7 (19).…”
Section: Members Of the Transforming Growth Factor-␤ (Tgf-␤)mentioning
confidence: 99%
“…Since ALK7 has been shown to mediate the effect of Nodal in mesoderm induction (19) and to activate Smad2 and Smad3 (23,25), we also examined mRNA expression of Nodal, Smad2, and Smad3. Similar to our previous studies that showed that Nodal mRNA is expressed in JEG-3 cells and in normal placenta (12), RT-PCR detected Nodal mRNA in JEG-3, JAR, JAR-Smad3/c, and HTR8/SVneo cells (Fig.…”
Section: Expression Of Alk7 Nodal and Smad Mrnas In Tropho-mentioning
confidence: 99%
“…The EGF-CFC co-receptor is essential for NODAL signaling by recruiting the convertases to the receptor complex site and facilitating NODAL binding to the ACVR1B/ACVR1C type I receptor (Blanchet et al 2008). Upon receptor complex formation, ACVR2A/ACVR2 phosphorylates ACVR1B/ACVR1C, which in turn phosphorylates the intracellular signal transducers SMAD2 or SMAD3 (Kumar et al 2001). SMAD2/3 then interacts with SMAD4 and additional transcription factors in the nucleus (e.g.…”
Section: Spc6mentioning
confidence: 99%